(untitled) (Docentes 2.0 Journal, 2023)
Techno-education is essential to achieve the human potential of the present in an egalitarian society, as well as the advancement of the nation-state. The objective of this essay was to exhibit a contrast of public policies in the techno-educational context with emphasis on the use of Artificial Intelligence (AI) present in the various continents that are committed to the progress of the creative potential of each individual. This essay was framed under the inductive method, hermeneutic paradigm, qualitative approach, interpretive type, and topical narrative design. Transformative education must guarantee that learners can access it without obstacles within a framework supporting Artificial Intelligence (AI). Therefore, education in various methods can adjust to the circumstances of collaborative digital technology. It means distorting long-term objectives and strategies that adapt to AI innovation within the framework of public policies.